Minneproblematikken i Lars Saabye Christensens lyrikk – analyse av jeg-personnens minner i lys av Memory Studies - Wilkus, Aleksandra Regina (Versita, 2013)
The purpose of this article is to perform an analysis of Lars Saabye Christensen’s poem ‘Nocturne’ from the perspective of Memory Studies. Recollections and the past are not simply the main issues of the literary work, but also provide a basis that can be used as a conceptual apparatus in one’s interpretative work. That is exactly what occurs in the relatively new study field that focuses on cultural aspects of literature, i.e. Memory Studies. Through an in-depth analysis of the language, stylistic measures, and with reference to Aristotle, I focus on the mechanisms that are in control of the lyrical subject’s memory. Just as essential are P. Ricoeur’s reflections on location and spatiality as well as A. Assman’s postulates that enable to describe objects and places as having a memory. The application of the ideas of Memory Studies as a methodological tool allows to determine the lyrical situation including the lyrical subject’s internal states.
Keywords: Lars Saabye Christensens; lyrikk; Nocturne; Memory Studies